2021
DOI: 10.31235/osf.io/j7qta
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Reliability of Replications: A Study in Computational Reproductions

Abstract: The paper reports findings from a crowdsourced replication. Eighty-four replicator teams attempted to verify results reported in an original study by running the same models with the same data. The replication involved an experimental condition. A “transparent” group received the original study and code, and an “opaque” group received the same underlying study but with only a methods section and description of the regression coefficients without size or significance, and no code. The transparent group mostly v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…[ 37 ] were replicated by researchers who specialize in mediation analysis, and these were two of the more replicable studies. Previous replication initiatives found that replicator expertise was indeed related to the reliability of a replication [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] were replicated by researchers who specialize in mediation analysis, and these were two of the more replicable studies. Previous replication initiatives found that replicator expertise was indeed related to the reliability of a replication [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%